Bone mineral density in type 2 diabetes mellitus determined by measurement of body mass index/handgrip strength ratio in a cross sectional study - Faheem Mahmood, Mudassar Ali, Sahar Mudassar, Shoaib Ahmed, Amna Mubeen, Muhammad Shahid Javed, Amal Shaukat, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diabetes mellitus (DM) causes substantial morbidity and death in most organs. Osteoporosis is a metabolic bone disease. Type 2 DM is associated to osteoporosis and muscular weakness (T2DM). However, research on type 2 diabetes and its impact on BMD and handgrip strength is sparse (HGS). Methods: The research involved 130 people aged 25–60. This is the Quetelet index. HGS was measured using a handgrip dynamometer. HGS max kg and ET in seconds were recorded. A bone sonometer measured BMD at the tibia's distal end. The T-score and Z-score were used to examine the results. Results: In diabetics, BMI correlated with BMD and HGS max (P = 0.032). BMD correlated weakly with HGS max and ET. Non-diabetic men had greater HGS, whereas non-diabetic females had higher HGS and ET (P <0.002). T2DM and non-diabetics had similar BMD. Conclusion: In our study, we noticed superior muscular strength among non-diabetics and no significant difference in BMD between diabetics and non-diabetics, but incidence of osteoporosis was larger among diabetics albeit statistically not significant.